Trastuzumab in Primary Inflammatory Breast Cancer (IBC): High Pathological Response Rates and Improved Outcome - Dawood, Shaheenah (2010)
Inflammatory breast cancer (IBC) represents a rare but aggressive and lethal form of locally advanced breast cancer (LABC) and frequently with HER-2 neu overexpressed or amplified. We retrospectively identified 16 newly diagnosed HER-2/neu-positive IBC patients who were treated with preoperative trastuzumab. We determined the pathological complete response rate (pCR) when trastuzumab was added to preoperative chemotherapy in patients with HER2/neupositive IBC. Furthermore, we assessed the expression of CXCR4 in metastatic recurrence sites. Ten patients (62.5%) achieved a pCR. Six patients (37.5%) achieved a partial response. Median follow-up of all patients was 24.2 months. Four (25%) patients have experienced a progression, of which three were in the brain. Two-year progression-free survival was 59.4% (95% CI 35–100). High expression of CXCR4 was detected in the brain metastases. We conclude that in spite of high pCR rates among women with HER-2/neu-positive IBC treated with neoadjuvant trastuzumab-based regimens the outcome remains dismal and brain recurrences are frequent. CXCR4 may represent a novel therapeutic target.